Auld Licht Idylls - Barrie, J. M. (James Matthew), 1860-1937 (Salt Lake City, UT : Project Gutenberg, 2007)
"Auld Licht Idylls" by J. M. Barrie is a collection of sketches and tales written in the late 19th century. The work explores life in a small Scottish community, particularly through the eyes of a schoolmaster who observes and interacts with the colorful inhabitants of the town of Thrums. The stories delve into local customs, the struggles of the working class, and the eccentricities of the community's characters. The beginning of "Auld Licht Idylls" introduces readers to the schoolhouse in the glen of Quharity, where a solitary schoolmaster navigates the challenges of a harsh winter. Starvation looms as animals struggle to find food, and he laments over his frozen bantam cock. The narrative captures a vivid imagery of the wintry landscape and provides insights into his loneliness, punctuated by interactions with animals and reflections on his life outside the glen. He anticipates the arrival of children back to school despite the snow, embodying a mix of charm and melancholy as he recounts the daily realities of life in Thrums. (This is an automatically generated summary.)
Release date is 2007-03-27
E-text prepared by Al Haines
Keywords: Scotland -- Social life and customs -- 19th century -- Fiction